2023
DOI: 10.3389/fpubh.2023.1125000
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness of myopia control interventions: A systematic review of 12 randomized control trials published between 2019 and 2021

Abstract: PurposeThis study aims to investigate the effectiveness of interventions to control myopia progression. In this systematic review, the primary outcomes were mean differences (MD) between treatment and control groups in myopia progression (D) and axial length (AL) elongation (mm).ResultsThe following interventions were found to be effective (p < 0.001): highly aspherical lenslets (HAL, 0.80 D, 95% CI, 0.77–0.83; −0.35 mm, 95% CI −0.36 to −0.34), MiSight contact lenses (0.66 D, 95% CI, 0.63–0.69; −0.28 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
0
7
0
3
Order By: Relevance
“…However, head-to-head comparisons revealed no statistical difference among atropine concentrations, except for 0.01% vs. 1% (MD, − 0.42; 95% CI − 0.71 to − 0.13) [ 48 ]. Similarly, in another recently published systematic review the estimated mean difference (MD) for myopia progression for atropine was found to be 0.29 D (95% CI 0.22–0.36; p = 0.03) [ 58 ]. In the present review, the most recent 16 out of initial 41 articles on RCTs were analyzed (Supplementary Table 3 ): a noticeable difference between these studies can be observed in terms of sample size [ 107 – 109 ], study length and design [ 110 114 ], the age of the children studied [ 106 , 109 ], location of trial [ 115 117 ], and the different atropine doses, which varied between 0.0025% and 1%, as well as the application frequency of drops [ 110 , 114 , 118 , 119 ], and lastly their aims [ 109 , 111 , 112 , 120 ].…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…However, head-to-head comparisons revealed no statistical difference among atropine concentrations, except for 0.01% vs. 1% (MD, − 0.42; 95% CI − 0.71 to − 0.13) [ 48 ]. Similarly, in another recently published systematic review the estimated mean difference (MD) for myopia progression for atropine was found to be 0.29 D (95% CI 0.22–0.36; p = 0.03) [ 58 ]. In the present review, the most recent 16 out of initial 41 articles on RCTs were analyzed (Supplementary Table 3 ): a noticeable difference between these studies can be observed in terms of sample size [ 107 – 109 ], study length and design [ 110 114 ], the age of the children studied [ 106 , 109 ], location of trial [ 115 117 ], and the different atropine doses, which varied between 0.0025% and 1%, as well as the application frequency of drops [ 110 , 114 , 118 , 119 ], and lastly their aims [ 109 , 111 , 112 , 120 ].…”
Section: Resultsmentioning
confidence: 98%
“…In children with faster myopia progression, effectiveness may improve with increased wear time, and with lens designs possessing higher hyperopic power in the mid-periphery (up to 6 D) [ 164 , 165 ]. In a recent meta-analysis Lanca et al [ 58 ] estimated the myopia progression mean differences (MD) for SCL at 0.39 D (95% CI 0.21, 0.56; p < 0.001); however, different types of myopia-controlling bifocal and multifocal SCL were included in this investigation. Besides the study reported by Lam et al, in which defocus incorporated soft contact (DISC) lenses reduced myopia progression by 60% [ 166 ], four more recently published RCTs about different SCL to reduce myopia progression were included in this review (Supplementary Table 5 ) [ 167 – 170 ]: The first reported results from a double-masked RCT conducted in multiple centers in China and North America involved approximately 200 children, randomly assigned to four arms: two prototype myopia control SCL with non-coaxial ring-focus designs, one for enhancing efficacy (EE) and one for enhancing vision (EV), compared to dual-focus and SV SCL.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent systematic review investigating the effectiveness of myopia control interventions by Lanca et al reported that low-dose atropine 0.01% was not effective in reducing AL progression in two studies at 12 months. Treatment efficacy with low-dose atropine of 0.05% showed good efficacy [ 21 ].…”
Section: Discussionmentioning
confidence: 99%